Perancangan Value Proposition Canvas untuk Produk Indibiz PT Telkom - Muhammad Haris Suwandi; Farda Hasun; Muhammad Almaududi Pulungan (MES Bogor, 2024)
This Indibiz is a digital service aimed at micro, small, and medium enterprises (MSMEs) in Indonesia. This service provides consistent and high-quality internet connectivity to support various MSME businesses. Indibiz is designed to offer affordable internet, helping to reduce operational costs and boost MSME productivity in the digital era. However, over the past year, Indibiz has not met its sales targets. The main cause is that Indibiz has yet to fully meet the desired customer profile. To address this, the author designed a Value Proposition Canvas by collecting data on Indibiz's services, customer profiles, and competitor products through observation, literature review, and interviews with 10 MSMEs. These data were used to create a customer profile and value map for Indibiz's products. A strategy canvas analysis and ERRC framework were applied to develop a new Value Proposition Canvas. The proposed solution includes adding an all-in-one MSME digitalization package, bundling digital marketing services, and offering a sales guarantee for each digitalization service purchase.